Investigative Auditing and Fraud: A Systematic Literature Review through a Theoretical and Bibliometric Lens - Suryani, Irma; Syahrudin, M. (Association of Certified Fraud Examiners Indonesia Chapter, 2025)
This study aims to examine the role of investigative auditing in detecting and disclosing fraud by identifying red flags within the context of increasing public scrutiny and expectation gaps in audit functions. Employing a Systematic Literature Review (SLR) combined with bibliometric analysis, the research utilizes Scopus-indexed journal articles published between 2015 and 2025, with the support of the Watase Uake platform to ensure structured article selection and keyword visualization. The study is grounded in the Expectation Gap Theory and Fraud Diamond Theory to analyze both behavioral and systemic dimensions of fraud. The findings reveal that although red flags such as lifestyle indicators and behavioral anomalies are widely acknowledged in fraud detection, current literature tends to focus more on traditional audit procedures than on the specific functions of investigative audits. Bibliometric mapping also highlights a concentration of studies around general fraud detection, with fewer focusing on the practical applications of investigative auditing. This paper provides novel insights by integrating theoretical analysis with bibliometric evidence, offering a clearer understanding of research gaps and future directions in investigative audit studies. The study adds value by reinforcing the importance of strengthening investigative audit capabilities and aligning them more closely with stakeholder expectations and the evolving nature of fraud.